Perencanaan Sistem Pengurangan Sampah Permukiman Bantaran Sungai Cidurian Kota Bandung - Raka Maulana; Yulianti Pratama; Lina Apriyanti (Jurnal Serambi Engineering, 2019)
Some areas in the city of Bandung is an area that dilitasi by the flow of the river, to prevent the introduction of garbage into the river basin is necessary to note the waste management systems in residential areas along the river. Cidurian river has a length of 24.86 Km along the river flow. Consists of the city of Bandung and Bandung regency. Administrative regions Cidurian River past eight (8) districts, from the region in the District Kiaracondong precisely Village Babakan Babakan Sari and Surabaya populous and the most densely populated. Thus, there should be community-based waste management in the form of a reduction in resources to prevent potential entry of waste into the river basin. Planning waste reduction will be divided into two, namely the reduction of inorganic waste with waste bank then the reduction of organic waste with absorption holes biopori, and bio reactor mini determination of the reduction is determined by the results of the analysis of the sampling covers the composition and garbage, then the result of the measurement characteristics test and analysis results questionnaire.